Sustainable land use framework: Ukraine case study - Nazarenko, V. (Land Management, Cadastre and Land Monitoring, 2024)
Under rapid urban expansion and continued use of natural land resources, it is necessary to study land use from several directions and complex data clusters.  For this purpose, the data and materials provided by the scientific community, as well as from government agencies and organizations and commercial companies, had been thoroughly examined, grouped and used in research. This methodology has proven to be effective in making the right assumptions and helping build an effective development framework model for the future development of land use. Land and forest resources undoubtedly play an important role in the formation and development of cities. The quality, sheer number and their use affect the economic development and environmental situation of cities in the surrounding areas. The available forest, food and land resources are especially important for large cities. Careful planning and consideration of various factors should be aimed at restoring land and natural resources, planning the costs of introducing new energy-saving and other technologies. The focus of this research work is the case study of urban land use under sustainable development program in Ukraine, based on pre 2023 data.  As a research outcome the author presents the sustainable land development framework. This framework should be considered a key part of the general urban development program. The result of using the proposed sustainable development program opens a possibility for a new land and city management policy that will result in nature resources preservation, in some case resources restoration and  public quality of live improvements.
Keywords: urbanization; sustainable development; land use planning; sustainability